2020
DOI: 10.1039/d0dt02756a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a novel nitrogen-doped carbon dot adorned zinc oxide composite for photodegradation of methylene blue

Abstract: Nitrogen-doped carbon dot decorated zinc oxide nanoparticles were successfully fabricated by an economical wet-impregnation method and used as a photocatalyst for the degradation of aqueous methylene blue dye under UV-light at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…reported N-CD decorated zinc oxide nanoparticles (N-CD@ ZnO) by a wet-impregnation method and used as a photocatalyst for the degradation of aqueous MB dye under UV-light. 150 Hu et al synthesized N-CQD (N-CQD) using different precursors with varying nitrogen contents and used in photocatalytic degradation of organic dyes such as indigo carmine (IC), ethyl violet (EV), CR, and bordeaux R (Bo-R). The degradation efficiency was 97% for IC under natural light for 2 h. 151 Chen et al developed a novel CQD modified potassium titanate nanotube (CQD/K 2 Ti 6 O 13 ) composite photocatalyst through hydrothermal treatment followed by calcination.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported N-CD decorated zinc oxide nanoparticles (N-CD@ ZnO) by a wet-impregnation method and used as a photocatalyst for the degradation of aqueous MB dye under UV-light. 150 Hu et al synthesized N-CQD (N-CQD) using different precursors with varying nitrogen contents and used in photocatalytic degradation of organic dyes such as indigo carmine (IC), ethyl violet (EV), CR, and bordeaux R (Bo-R). The degradation efficiency was 97% for IC under natural light for 2 h. 151 Chen et al developed a novel CQD modified potassium titanate nanotube (CQD/K 2 Ti 6 O 13 ) composite photocatalyst through hydrothermal treatment followed by calcination.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…The results indicate that the activity of N-CD@ZnO composite slightly decreases the MB degradation from 99% to 95% after three runs. 150 Sui et al loaded CQD on TiO 2 nanosheets (CQD/TiO 2 -001) for visible light assisted photocatalytic activity for H 2 evolution from methanol aqueous solution under a 300 W xenon lamp irradiation. The cycling test results of the photocatalytic activity of synthesized CQD/ TiO 2 -001 for H 2 evolution was checked, and it was found that H 2 evolution rate is maintained even after eight cycles, supporting a great stability of the synthesized CQD/TiO 2 -001 in the photocatalytic H 2 evolution under the simulated solar light irradiation.…”
Section: Stability and Recyclability Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then N-CDs with the up-conversion properties convert the long-wavelength light to the short-wavelength light that can excite ZnO to form separate electrons and holes. During the degradation process of the MB dye, the π-π* interaction between N-CDs and the MB dye can enhance the degradation of MB by the N-CDs@ZnO photocatalyst [ 125 ]. The nitrogen-rich carbon nitride (p-C3N5) had exceptional electronic properties.…”
Section: Applications Of Cdsmentioning
confidence: 99%
“…The N-CDs@ZnO composite showed a higher photocatalytic degradation activity of MB under UV irradiation, which was 2.3 times higher than that of pure ZnO nanoparticles. 43 Song et al 44 prepared NPCQD modified multi-shell ZnO microsphere photocatalysts (NPCQD/ZnO). Under simulated sunlight conditions, the photodegradation performance of 2g-NPCQD/ZnO composites for MB is better than that of pure ZnO.…”
Section: Introductionmentioning
confidence: 99%